2016
DOI: 10.15218/zjms.2016.0010
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparison of transvaginal, transabdominal ultrasound and diagnostic curettage in the evaluation of endometrial pathology

Abstract: Background and objective: Abnormal uterine bleeding due to endometrial abnormalities is a common diagnostic challenge facing the radiologist and referring gynecologist. This study was aimed to compare the diagnostic performance of transvaginal ultrasound, transabdominal ultrasound and diagnostic curettage in the detection of endometrial pathologies in symptomatic women. Methods: A prospective comparison study of transvaginal ultrasound, transabdominal ultrasound and diagnostic curettage was conducted for evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…22 Another study done in our locality in Erbil showed sensitivity and specificity of vaginal ultrasound in the detection of endometrial pathologies were 100% and 94.7%. 25 Another study done by Showkat et al showed a sensitivity of transvaginal ultrasound in the detection of endometrial carcinoma of 67%, specificity 100%, accuracy 98%, positive predictive value 100% and negative predictive value 97%. 26 Transvaginal sonographic scanning is gold slandered investigation for postmenopausal women with vaginal bleeding.…”
Section: Discussionmentioning
confidence: 97%
“…22 Another study done in our locality in Erbil showed sensitivity and specificity of vaginal ultrasound in the detection of endometrial pathologies were 100% and 94.7%. 25 Another study done by Showkat et al showed a sensitivity of transvaginal ultrasound in the detection of endometrial carcinoma of 67%, specificity 100%, accuracy 98%, positive predictive value 100% and negative predictive value 97%. 26 Transvaginal sonographic scanning is gold slandered investigation for postmenopausal women with vaginal bleeding.…”
Section: Discussionmentioning
confidence: 97%
“…In postmenopausal women, because the endometrium undergoes a long period of exposure to risk factors, the etiology of PMB may be due to benign, such as atrophy, endometritis or EH, but these women show a higher percentage of malignancy than perimenopausal women. 19 , 20 , 21 , 22 , 23 Because our study did not involve clinical intervention, only patients with histopathological results were recruited, and these results were compared with the ultrasound results. Participants lacking histopathological results were excluded from the study; therefore, endometrial atrophy and normal endometrium were rare in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite existing difference in study population, generally, menorrhagia is still the common type of bleeding in perimenopausal women with AUB. [ 34 35 36 ] Dilation and curettage by Karman cannula is considered as an adequate method for the hemorrhagic treatment and endometrial sampling biopsy, thus, almost cases underwent this interventional procedure in our study [ Figure 3 ]. [ 37 ] According to Gupta et al ., the use of Karman cannula resulted in less pain and is a much cheaper option in comparison to Pipelle.…”
Section: Discussionmentioning
confidence: 99%